Heterogeneity in Psychological Adaptation Patterns and Its Predictive Factors Among Patients with Inflammatory Bowel Disease: A Latent Profile Analysis - Xu G; Liu T; Jiang Y; Xu Y; Zheng T; Li X (Psychology Research and Behavior Management, 2024)
Guangyi Xu,1 Ting Liu,1 Yunxia Jiang,1 Yanhong Xu,2 Taohua Zheng,2 Xiaona Li3 1Author affiliations School of Nursing, Qingdao University, Shandong, People’s Republic of China; 2Author affiliations Department of Gastroenterology, The Affiliated Hospital of Qingdao University, Shandong, People’s Republic of China; 3Author Affiliations Endoscopic Diagnosis and Treatment Center, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Qingdao, People’s Republic of ChinaCorrespondence: Ting Liu, School of Nursing, Qingdao University, 1 Ningde Road, Qingdao, Shandong, 266073, People’s Republic of China, Tel +86 15066237573, Email liuting201516@163.comPurpose: To identify the distinct profiles of psychosocial adaptation of Chinese inflammatory bowel disease (IBD) patients and the predictive factors.Patients and Methods: A cross-sectional survey method was used to recruit 263 IBD patients who were treated in a tertiary hospital in Shandong Province from July 2022 to April 2023. The general information questionnaire, Inflammatory Bowel Disease Psychosocial Adaptation Questionnaire, Resilience Scale for Inflammatory Bowel Disease, Chinese Benefit Finding Scale, and Stigma Scale for Chronic Illnesses, Medical Coping Modes Questionnaire and Inflammatory Bowel Disease-Disk were used as the instruments for investigation. Latent profile analysis was conducted with the six dimensions of the IBD Psychosocial Adaptation Questionnaire as the explicit indicators. The predictors of profile membership were analyzed by multinomial logistic regressions.Results: Four profiles of psychosocial adaptation in IBD patients were identified: Low level psychosocial adaptation (14.1%), Medium level psychosocial adaptation – High body image distress (25.5%), Medium level psychosocial adaptation – Low body image distress (30.0%) and High level psychosocial adaptation (30.4%). Compared with Low level psychosocial adaptation group, High level psychosocial adaptation group had a higher level of positive cognition (OR=2.930, 95%IC 0.017– 0.305, p< 0.001) and overall psychological resilience (OR=1.832, 95%IC 0.000– 0.016, p < 0.001), more health behaviors (OR= 2.520, 95%IC 0.191– 1.358, p=0.001), a lower level of internal stigma (OR=0.135, 95%IC 0.043– 0.420, p < 0.001) and overall stigma (OR=0.010, 95%IC 0.003– 0.118, p=0.001), less acceptance-resignation coping style (OR=0.055, 95%IC 0.209– 3.200, p < 0.001) and lower disease burden (OR=0.407, 95%IC 0.298– 0.698, p=0.006).Conclusion: About a half of IBD patients had a medium level of psychosocial adaptation. Psychological resilience, benefit finding, stigma, medical coping styles and disease burden predicted psychosocial adaptation profiles. Healthcare providers need to focus on the heterogeneity of psychosocial adaptation of IBD patients and formulate personalized intervention programs for patients with different profiles to improve their psychosocial adaptation.Keywords: inflammatory bowel disease, latent profile analysis, psychosocial adaptation, benefit finding, resilience, coping, stigma